ANTIHYPERGLYCHEMIC ACTIVITY TEST OF EXTRACT, METHANOL FRACTION AND N-HEKSAN FRACTION OF KETAPANG LEAF (Terminalia catappa) IN ALLOXAN-INDUCED WHITE RATS - Rachma Nurhayati (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Background: Ketapang leaf (Terminalia catappa) can be used as a traditional medicine that has the potential activity to reduce blood glucose levels in the body. Objective: To determine the activity of extracts and fractions of ketapang leaves in reducing blood glucose levels of rats induced by alloxan. Methods: This study was an experimental study using 30 male wistar rats as test animals divided into 6 groups. Group I was healthy control, group II was negative control (K-) that given 0.5% Na CMC solution, group III was positive control (k+) that given metformin suspension, groups IV, V, and VI were given ketapang leaf extract, methanol fraction and n-hexane fraction, respectively. Results: The ethanol extract and methanol fraction of ketapang leaves can reduce blood glucose levels in white rats because they contain flavonoid compounds which are thought to have antihyperglycemic activity. Conclusions: The methanol fraction of ketapang leaves (Terminalia catappa) was most effective in reducing blood glucose levels in alloxan-induced white rats.